Introduction: The Cynics, Optimists and Pirates are all Making Africa Beautiful - Onyango-Obbo, Charles (Development, 2012)
There are two dominant positions about Africa today and in the near future: on the one side, a heady optimism that envisions ‘Africa Rising’, and on the other a cynicism that sees a continent still trapped in‘darkness’. In between you find the simply weary, mildly celebratory, and nearly indifferent. The majority of articles in this issue hug the vast middle; there is shy pessimism, cautious optimism, but also recognition that Africa’s development has not and probably will not be linear, and interesting possibilities could ^ ormight not ^ emerge as nationsmuddle along. And even where outcomes have been disastrous, and nations starved and people killed or oppressed, there is some acknowledgement that most of Africa’s Big Men (it has been men for the most part) set out with good intentions. Together, this search for new vantage points to evaluate the continent, the recognition that enough of ‘old Africa’still persists to justify pessimism, but also that optimism about the continent has not been snuffed out by the failures and disappointments of recent decades, is beautiful to see.This is because these various outlooks prevent a slide into the complacency and insularity that are often born of an overblown sense of achievement, or the despair that can be bred by pessimism.
Keywords: Introduction; Cynics; Optimists; Pirates; Africa